2018
DOI: 10.1093/eurheartj/ehy319
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of low-density lipoprotein particles to aggregate depends on particle lipidome, is modifiable, and associates with future cardiovascular deaths

Abstract: AimsLow-density lipoprotein (LDL) particles cause atherosclerotic cardiovascular disease (ASCVD) through their retention, modification, and accumulation within the arterial intima. High plasma concentrations of LDL drive this disease, but LDL quality may also contribute. Here, we focused on the intrinsic propensity of LDL to aggregate upon modification. We examined whether inter-individual differences in this quality are linked with LDL lipid composition and coronary artery disease (CAD) death, and basic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
171
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(186 citation statements)
references
References 45 publications
9
171
0
6
Order By: Relevance
“…We have previously shown that 277 intake of CSO decreases serum LDL cholesterol compared with the fatty fish and lean fish 278 groups and IDL particle concentration compared with the lean fish group [25,32]. Taken [8]. Here, we found no change in the LDL aggregation among 287 the groups, but it should be noted that the individual differences in LDL aggregation were 288 large, as also reported earlier [8].…”
supporting
confidence: 80%
See 3 more Smart Citations
“…We have previously shown that 277 intake of CSO decreases serum LDL cholesterol compared with the fatty fish and lean fish 278 groups and IDL particle concentration compared with the lean fish group [25,32]. Taken [8]. Here, we found no change in the LDL aggregation among 287 the groups, but it should be noted that the individual differences in LDL aggregation were 288 large, as also reported earlier [8].…”
supporting
confidence: 80%
“…The susceptibility of LDL to aggregation has recently been shown to differ significantly 232 among human donors and to be associated with cardiovascular deaths [8]. Here, we again 233 found significant individual differences in LDL aggregation, but found no statistically…”
Section: Ldl Aggregation 231mentioning
confidence: 45%
See 2 more Smart Citations
“…30,55 This concept is supported by the notion that a common underlying trait connecting lipoprotein metabolism to heart disease risk is the extent to which the condition influences the duration of exposure to arterial tissue, due to either the properties of the LDL-P (e.g., small LDL) or to reduced hepatic LDL receptor expression (e.g., in familial hypercholesterolemia). Further traits that have been associated with potentially higher atherogenicity of small LDL-P include compositional and conformational changes that render them more prone to retention, 64 aggregation, 65,66 and oxidation 64 in the arterial wall. Overall, there is not incontrovertible evidence supporting the concept that particle for particle, a small LDL-P (<25 nm) is more atherogenic than a large LDL-P.…”
Section: Insulin Resistance/compensatory Hyperinsulinemia/prediabetesmentioning
confidence: 99%